2016
DOI: 10.1080/1059924x.2016.1143903
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Silence: Sexual Harassment of Mexican Women Farmworkers

Abstract: The purpose of this study was to understand Mexican women farmworkers’ perceptions of workplace sexual harassment, its related factors and consequences, and potential points of intervention. This community-based participatory research study conducted focus groups with 20 women farmworkers in rural Washington. Four coders analyzed and gleaned interpretations from verbatim transcripts. Three main themes were identified. It was learned that women farmworkers: (1) frequently experienced both quid pro quo and hosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 31 publications
2
37
0
5
Order By: Relevance
“…However, we were surprised to see that the occupational risk factors of years in agricultural work and payment method were associated with AKI in women in our sample. Studies of women's experiences in agricultural work have documented the risk of sexual harassment or assault, which often occurs around bathroom facilities 45 46. Women may tend to limit drinking or eating during their work shift to reduce their need to use these facilities, or may delay trips to the bathroom during the work day out of fear for their safety.…”
Section: Discussionmentioning
confidence: 99%
“…However, we were surprised to see that the occupational risk factors of years in agricultural work and payment method were associated with AKI in women in our sample. Studies of women's experiences in agricultural work have documented the risk of sexual harassment or assault, which often occurs around bathroom facilities 45 46. Women may tend to limit drinking or eating during their work shift to reduce their need to use these facilities, or may delay trips to the bathroom during the work day out of fear for their safety.…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51][52] Some participants in this study understood disregard for tomato workers' health to signify that employers saw workers as entities to be used for production, like tools or livestock, rather than as fully human beings meriting protection and care, which is consistent with other recent studies of agricultural working conditions and ethical critiques of contemporary agricultural labor systems. [52][53][54][55][56] This study and numerous others have confirmed that supervisors' misconduct harms farmworkers' wellbeing; [51][52][53]57,58 this study contributes to the literature with the finding that the support of workers' organizations promotes supervisory practices notable for greater respect for tomato workers' just compensation, health, and dignity. With organizational support, workers in certain regions have a means to advocate collectively for fair wages and safer working conditions with less risk of employer retaliation.…”
Section: Discussionmentioning
confidence: 67%
“…They confirmed that tomato workers experience financial insecurity stemming from work organization factors at multiple levels, including seasonal and weatherdependent work hours, wage theft, employment insecurity exacerbated by the threat of employer retaliation, lack of economic opportunities in countries of origin, and lack of governmentsanctioned work authorization in the United States. 40,[56][57][58][66][67][68] Though not discussed in depth in this study, discrimination based on citizenship and ethnicity is another known societal-level factor that prevents immigrant and ethnic minority farmworkers from securing safer and more stable employment. [51][52][53][54][55]68,69 Thus, farmworkers not only lack control over their immediate working conditions, they also lack options regarding how they participate in the global labor market.…”
Section: Discussionmentioning
confidence: 99%
“…These women are especially vulnerable due to a number of factors structural to the U.S. agricultural industry, including "being female in a male-dominated industry, living in poverty, language barriers, being an immigrant, being an indigenous immigrant and oftentimes lacking work authorization" (Kominers 2015, 4). The vast majority of these women do not report the assaults for fear of workplace retaliation, job loss, and deportation (Bauer and Ramirez 2017;Kim et al 2016;Kominers 2015). Throughout all of this, these women farmers earned only an average of $11,250/year (compared to $16,250 for men) (Kominers 2015, 4).…”
Section: Relational Agriculture and Food Justicementioning
confidence: 99%